Artificial Intelligence and Islamic Education: A Theoretical Review - Bhenu Artha; Fajar Santoso; Bahri Bahri; Cahya Purnama Asri; Utami Tunjung Sari; Niken Permata Sari; Ascasaputra Aditya (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2025)
As these potent technologies develop further, AI offer previously unheard-of opportunities as well as difficult problems that demand careful consideration. It is impossible to overestimate the significance of AI in education. In order to ensure that AI's transformational potential is utilized for the benefit of society as a whole, we therefore seek to contribute to the development of a responsible and ethical approach to its application. In order to accomplish the goals and objectives of the research, a theoretical literature survey is carried out, and a conceptual framework for further investigation is provided. Islamic education is viewed by the authors of the current study as a dependent variable that is influenced by artificial intelligence. A future where AI in education catalyzes good change and enables people and communities to realize their full potential will be created by promoting equal access to AI-driven tools, encouraging interdisciplinary cooperation, and engaging in open discourse.